Epidural Fibrosis Seen from a Different Angle: Extraforaminal Lumbar Interbody Fusion - Kurzbuch, Arthur Robert; Recoules-Arche, Didier (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Postoperative epidural fibrosis (PEF) localized around the exposed dura and nerve roots is a known radiologic entity seen after lumbar surgery. Although excessive PEF is associated with residual and new lumbar pain and radiculopathy, its role as the generator of the pain is still discussed. Various materials acting as an adhesion barrier have been tested. There is no undebated class I evidence that any one of them is suitable to reduce or avoid PEF and provide a better clinical outcome. In revision surgery, the dissection of epidural scar tissue is time consuming and related to an elevated risk of dural tear and nerve damage. To avoid the formation of posterior PEF, we propose a surgical approach whose working corridor is situated lateral to the dural sac and the nerve roots: the extraforaminal lumbar interbody fusion (ELIF) technique.Methods Description of ELIF surgical technique.Conclusions The ELIF technique is a muscle-sparing approach to the intervertebral disk space and the spinal canal that avoids the formation of posterior PEF. It represents an option to treat various degenerative lumbar spinal diseases as well as offering another approach for revision surgery in patients who have developed PEF.
Keywords: epidural fibrosis; complication; lumbar interbody fusion; muscle preservation; extraforaminal approach